2020
DOI: 10.1159/000506691
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Risk Factors of Inflammatory Breast Cancer according to Luminal, HER2-Overexpressing, and Triple-Negative Subtypes: A Case Comparison Study

Abstract: Objective: We evaluated the risk factors of inflammatory breast cancer (IBC) compared to non-IBC and according to histological subtype. Methods: Cases of IBC (n = 160) and controls of non-IBC (n = 580) were collected from the cohort of breast cancer patients treated in two oncology centers matched based on age at cohort entry. Data about breast cancer risk factors were collected. We evaluated correlation and ORs using conditional logistic regression analysis for each case group versus the control group. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Most importantly, IBC is a NIH-designated cancer health disparity ( Institute, 2016 ) with increased global incidence and mortality in minoritized and marginalized populations ( Relation et al, 2021 , Schinkel et al, 2014 , Gudina et al, 2019 ). This is consistent with reports of distinct reproductive risk factors like younger age at first pregnancy, multiparity, and breastfeeding in IBC ( Fouad TM, 2018 ) ( Linhares et al, 2020 , Mejri et al, 2020 ). These studies highlight the significance of primary care providers (PCP), including physicians, physician assistants, and nurse practitioners, who are often the first point of contact when patients begin to notice symptoms ( Nekhlyudov et al, 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…Most importantly, IBC is a NIH-designated cancer health disparity ( Institute, 2016 ) with increased global incidence and mortality in minoritized and marginalized populations ( Relation et al, 2021 , Schinkel et al, 2014 , Gudina et al, 2019 ). This is consistent with reports of distinct reproductive risk factors like younger age at first pregnancy, multiparity, and breastfeeding in IBC ( Fouad TM, 2018 ) ( Linhares et al, 2020 , Mejri et al, 2020 ). These studies highlight the significance of primary care providers (PCP), including physicians, physician assistants, and nurse practitioners, who are often the first point of contact when patients begin to notice symptoms ( Nekhlyudov et al, 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…Black women are disproportionately impacted by IBC and are more likely to be diagnosed with triple negative-IBC and a worse outcome than any other racial group. 33,[38][39][40][41][42][43] Underrepresentation of black women in our cohort precludes analysis of classic presentation by race; no significant associations were observed in our analysis, however, this limitation makes it inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal models of mammary tumorigenesis and pregnancy have confirmed the protective effects of pregnancy in BC (Feigman et al, 2020;Hanasoge Somasundara et al, 2021). Interestingly, prolonged lactation and nursing have also been identified as key risk factors for inflammatory breast cancer (IBC), a rare and highly aggressive BC subtype (Mejri et al, 2020). On the other hand, studies have shown that short-term breast feeding and premature involution may also contribute to a "primed" stroma that is permissive to IBC (Bambhroliya et al, 2018).…”
Section: Loss Of Irf5 Expression Alters Normal Mammary Gland Developm...mentioning
confidence: 99%